EFEKTIVITAS PENATAAN ORGANISASI SEKRETARIAT DAERAH KOTA TOMOHON - ROMPIS, FRANDO; Laloma, Alden; Plangiten, Novva (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : Since the enactment of PP. 41 Year 2007 on Regional Perengkat organizations, localgovernments Tomohon has conducted reorganization regional secretariat. Accordingly, this research toknow "how the effectiveness of the arrangement of regional organizations secretariat Tomohon areasthat exist today.Research using qualitative methods. Informants in this study were taken from the executive officersand employees of the Regional Secretariat of Tomohon, the district secretary, the assistant secretary ofthe area, two heads of sections, subsections two heads, and two executive employees / staff. Datacollection by interview; while the analysis of data using analysis techniques interactive model of Milesand Hubernann.Based on the results of the study conclude that the Regional Secretariat organizational structuringTomohon have been effective. In other words, the organization secretariat Tomohon area that is nowable to create or realize the implementation of the basic tasks and functions of the secretariat of thearea effectively. The effectiveness of the arrangement organaisasi secretariat area Tomohon can bedemonstrated by several criteria: rationality, according to need, efficiency, can function optimally, cantarget the optimal results, it can use the budget appropriately and efficiently, is able to anticipate thedevelopment and enhancement task / job, and is able to overcome the problems or barriers / obstaclesthat arise in the implementation of tasks and functions.Based on the conclusions of the research results it is suggested that the organization needs analysis isalways done periodically and continuously so that the future organization of the secretariat ofTomohon area will be more effective in carrying out the duties and functions as mandated by thelegislation in force.Keywords: effectiveness, organizational management